THE INFLUENCE OF MOTIVATION, CAREER DEVELOPMENT AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. PELABUHAN INDONESIA (Persero) REGIONAL 4 MAKASSAR - Muhammad Nuzul Hidayat; Indrianty Sudirman; Jusni Jusni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2022)
The aim of this study: (1) To find out and analyze the influence of motivation on employee performance. (2) To find out and analyze the effect of career development on employee performance. (3) To find out and analyze the influence of leadership style on employee performance. (4) To find out and analyze career development, motivation, and leadership style on employee performance. (5) To find out and analyze the most dominant variable that affects employee performance at PT. Pelabuhan Indonesia (Persero) Regional 4 Makassar. Data collection was carried out at PT. Pelabuhan Indonesia (Persero) Regional 4 Makassar. Research population of all employees of PT. Pelabuhan Indonesia (Persero) Regional 4 Makassar as many as 1.545 employees. Sampling using the Slovin formula so that the number of samples is 94 respondents. Research results show that: (1) Motivation has a positive and significant effect on employee performance. (2) Career development has a positive and significant effect on employee performance. (3) leadership style has no significant effect on employee performance. (4) Simultaneously or together the variable of career development, motivation, and leadership style have a positive and significant influence on employee performance. (5) Career development variable is the dominant factor influencing employee performance at PT. Pelabuhan Indonesia (Persero) Regional 4 Makassar.